Impact of VO2max on mechanical variables, lactic acid concentration and shooting accuracy of the 7-meter throw among handball players - Ibtehal Mohammad Alkhawaldeh (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.